Standardization of Vellarugu Chooranam, a Siddha Herbal Drug - Vinotha, S.; Ira, T.; Sri Ranjani, S. (1 st International Conference on Unani, Ayurveda, Siddha and Traditional Medicine - 2013, 2013)
Standardization of herbal formulation is essential in order to assess the quality of drugs, based on the concentration of their principles. Vellarugu Chooranam is a reputed drug mentioned in the ancient books of Siddha Medicine for the treatment of vata diseases, arthritis, constipation, and diabetes mellitus. The main constituent of chooranam is whole plant of Eincostemma littorale Blume. For the standardization of this drug Organoleptic properties, Phytochemical screening , Fluorescence analysis, Elemental analysis, physicochemical parameters such as moisture content,ash values, extractability in water and ethanol were carried out. TLC and HPLC fingerprints of the chooranam were also prepared to help evaluate its quality. The total ash, water soluble ash, acid insoluble ash, sulfated ash, pH and moisture content were found to be 8.16 ± 0.1%, 2.75 ± 0.1%, 1.30 ± 0.1%, 5.12 ± 0.02 and 10.25 ± 0.33% respectively. The percentage yields of hot and cold water extractable matter (37.21 ± 1.27% & 28.67 ± 0.58) were greater than hot and cold ethanol extractable matter (24.92 ± 0.64 % & 12.68 ± 0.99). The phytochemical screening of hot and cold aqueous and ethanol extracts showed the presence of alkaloids, saponins, flavonoids, steroids, tannins, proteins, carbohydrates, coumarins and quinones. The presence of heavy metals in the chooranam was below the WHO/ FDA permissible limits. In the TLC profile, the best separation of the hot and cold ethanol extractsoccurred inMethanol, Dichlo9romethane, Cyclohexane (0.2:5,8:4 v/v)solvent system as the mobile phase. These parameters were found to be sufficient to evaluate authenticity of the chooranam and can be used as reference standards for the preparation of a standardized pharmaceutical product.
Keywords: Herbal Drug; Parameters; Siddha Medicine; Standardization; Vellarugu Chooranam